TEXT COMPREHENSION AND INTERPRETATION - da Silva, Rosiane Pereira (Seven Editora, 2026)
This chapter addresses the fundamental concepts of text comprehension and interpretation, emphasizing the importance of reading as an interactive process between text, reader, and socio-historical context. Text is defined as a linguistic manifestation produced with a specific communicative intention and directed at a specific interlocutor, being constructed from linguistic, contextual, and intentional factors. It highlights that reading depends not only on the characteristics of the text, but also on the reader’s experiences, knowledge, and context. Thus, textual comprehension results from the interaction between the textual content and the individual’s prior knowledge, making reading a dynamic and meaningful process. Another central point discussed is the role of prior knowledge in reading comprehension. It also emphasizes inference as an essential cognitive strategy for textual comprehension. In conclusion, the importance of pedagogical planning in Portuguese language teaching is highlighted, emphasizing that the prior organization of classes contributes to a more efficient and meaningful teaching practice in the teaching-learning process.